Integration of PjBL STEM Based Digital Teaching Materials in High School Physics Learning: Opportunities and Challenges in the Digital Era - Eka Puji Astuti; Nurul Fitiyah; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2024)
This study aims to examine the integration of digital teaching materials based on Project-Based Learning (PjBL) combined with the STEM approach in high school physics learning. The method used is a qualitative literature review by analyzing 16 national and international journal articles published between 2015 and 2024, which were selected based on relevance to the topic, methodological clarity, and the presence of empirical. The results indicate that digital teaching materials enhance the quality of learning through interactive, flexible, and contextual content delivery. The implementation of the PjBL model promotes active student engagement, improves collaboration skills, and facilitates the application of physics concepts in real-life contexts. Meanwhile, the STEM approach contributes to the development of critical thinking, creativity, and problem-solving skills. The integration of digital teaching materials, PjBL, and STEM is proven to be more effective than their separate implementation, as it connects theory and practice comprehensively. However, its implementation still faces challenges such as limited technological facilities and user readiness. Therefore, well-designed instructional planning and institutional support are required to optimize its implementation in improving the quality of physics learning.